2001
DOI: 10.1177/000348940111000115
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Mediates Platelet Activating Factor-Induced Microvascular Leakage in Rat Airways

Abstract: Platelet activating factor (PAF), a highly potent chemical mediator in inflammation and allergic reactions, induces microvascular leakage in several tissues. In rat airways, PAF-induced microvascular leakage is probably mediated by an endothelial cell receptor in the microvessels. Nitric oxide (NO), first identified as endothelium-derived relaxing factor, has been suggested to be a mediator of airway microvascular leakage. However, the role of NO in PAF-induced microvascular leakage in the airways has not yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…One possible explanation is that this differential regulation of NO represents another example of the frequently contrarian regulatory mechanisms of the systemic and the pulmonary circulation, for example high versus low arterial blood pressure or hypoxic dilatation versus hypoxic constriction. However, that would not explain why NO donors are protective against PAF-induced oedema in both the lungs [16] and the intestine [36]. Alternatively, these differences might be explained in terms of the bell-shaped dose-response curve of NO where either too little or too much NO increases vascular permeability.…”
Section: Role Of No In Paf-induced Oedema Formationmentioning
confidence: 96%
See 2 more Smart Citations
“…One possible explanation is that this differential regulation of NO represents another example of the frequently contrarian regulatory mechanisms of the systemic and the pulmonary circulation, for example high versus low arterial blood pressure or hypoxic dilatation versus hypoxic constriction. However, that would not explain why NO donors are protective against PAF-induced oedema in both the lungs [16] and the intestine [36]. Alternatively, these differences might be explained in terms of the bell-shaped dose-response curve of NO where either too little or too much NO increases vascular permeability.…”
Section: Role Of No In Paf-induced Oedema Formationmentioning
confidence: 96%
“…Probable reasons to explain conflicting reports showing either attenuation [16] or aggravation [29,30] of pulmonary oedema by NO synthase inhibitors are: 1) the different timing of the measurements; 2) the numerous and diverse effects of NO on leukocytes and endothelial cells; and 3) the notion that both too much and too little NO can increase vascular permeability [11]. The model of the isolated blood-free perfused rat lung allows circumvention of most of these confounders.…”
Section: Role Of No In Paf-induced Oedema Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which PAF increases vascular permeability is not clearly understood although there is evidence that PAF-induced leakage is associated with activation of protein kinase C [12, 13]and tyrosine kinase pathways [14], and opening of L-type calcium channels [15]. Furthermore, studies have shown that PAF-induced leakage can be attenuated by inhibitors of nitric oxide synthase (NOS) [16, 17, 18]or by scavenging reactive oxygen species (ROS) [7, 9, 11, 19]suggesting that both NO and ROS are involved in PAF-induced leakage. The relationship between PAF and NO is particularly interesting in the hamster cheek pouch microcirculation because, while NOS inhibition attenuates PAF-induce leakage, it is not because NO mediates the leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that PAF stimulates nitric oxide synthase (NOS) to release nitric oxide (NO) and that PAF actions are mediated by this endogenous NO in endotoxic shock, cardiopulmonary actions, microvascular permeability, and bowel injury in animal experiments. 24–28 NO is produced by a family of NOS, including neuronal NOS (nNOS, type 1), inducible NOS (iNOS, type 2), and endothelial NOS (eNOS, type 3). All three major isoforms of NOS have been demonstrated immunohistochemically in different cells of the organ of Corti and other parts of the auditory systems of guinea pigs.…”
Section: Introductionmentioning
confidence: 99%